Development of improved method to identify and analyze lung fibrocytes with flow cytometry in a reporter mouse strain. Issue 1 (24th December 2020) - Kawano, Hiroshi; Koyama, Kazuya; Nishimura, Haruka; Toyoda, Yuko; Kagawa, Kozo; Sato, Seidai; Naito, Nobuhito; Goto, Hisatsugu; Inagaki, Yutaka; Nishioka, Yasuhiko
Abstract: Introduction: Fibrocytes are emerging myeloid‐derived circulating cells that can migrate into damaged tissues and usually contribute to their repair. Key features of fibrocytes include the expression myeloid markers, production of extracellular matrix proteins, and secretion of various humoral factors that activate resident fibroblasts; they also have the potential to differentiate into fibroblasts. However, no specific surface markers have been identified to identify fibrocytes in vivo. One reason could be that the method used to detect fibrocytes requires intracellular collagen staining. Methods: In the present study, to establish an improved method for the detection of lung fibrocytes and to analyze viable fibrocytes, we used collagen I(α)2‐green fluorescent protein (Col‐GFP) reporter mice, which had undergone the intratracheal instillation of bleomycin (BLM). Results: Using flow cytometry to gate out cells with autofluorescence, we clearly found that CD45 + GFP +  cells resided in the lungs of Col‐GFP mice at a steady state and these cells increased after BLM injury, peaking at Day 14. These cells expressed not only known cell surface markers of fibrocytes, but also some novel markers, in addition to a low level of collagen I in comparison to CD45 − GFP +  cells. Conclusion: Our findings suggest that the improved method can be a useful for the detection of pure lung fibrocytes and allows us to further analyze the characteristics of viable fibrocytes. Abstract : In this report, we established improved method for detection of lung fibrocytes. Using flow cytometry to gate out cells with autofluorescence and combine expression pattern of CD11b, CD11c, Gr‐1, we clearly found fibrocytes resided in lungs.